2012
DOI: 10.1073/pnas.1210422109
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage tissue engineering using differentiated and purified induced pluripotent stem cells

Abstract: The development of regenerative therapies for cartilage injury has been greatly aided by recent advances in stem cell biology. Induced pluripotent stem cells (iPSCs) have the potential to provide an abundant cell source for tissue engineering, as well as generating patient-matched in vitro models to study genetic and environmental factors in cartilage repair and osteoarthritis. However, both cell therapy and modeling approaches require a purified and uniformly differentiated cell population to predictably reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
257
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(268 citation statements)
references
References 51 publications
10
257
1
Order By: Relevance
“…122 iPSCs generated from the reprogramming of mouse fibroblasts have been successfully differentiated toward the chondrogenic linage, and shown to integrate with native cartilage tissue and produce cartilage matrix in an in vitro cartilage defect model. 123 Furthermore, chondrogenic differentiation of MSC-like cells derived from human iPSCs has been shown by Guzzo et al to result in a cellular phenotype that more closely resembles articular chondrocytes, compared with undifferentiated iPSCs. 124 iPSCderived MSCs inhibit lymphocyte proliferation and suppress Th2-associated cytokine production in a similar manner to MSCs, and have been found to elicit a comparable immunomodulatory effect in a mouse model of allergic inflammation.…”
Section: Cell Therapymentioning
confidence: 99%
“…122 iPSCs generated from the reprogramming of mouse fibroblasts have been successfully differentiated toward the chondrogenic linage, and shown to integrate with native cartilage tissue and produce cartilage matrix in an in vitro cartilage defect model. 123 Furthermore, chondrogenic differentiation of MSC-like cells derived from human iPSCs has been shown by Guzzo et al to result in a cellular phenotype that more closely resembles articular chondrocytes, compared with undifferentiated iPSCs. 124 iPSCderived MSCs inhibit lymphocyte proliferation and suppress Th2-associated cytokine production in a similar manner to MSCs, and have been found to elicit a comparable immunomodulatory effect in a mouse model of allergic inflammation.…”
Section: Cell Therapymentioning
confidence: 99%
“…A typical example of cartilage regenerative medicine is autologous chondrocyte implantation, in which chondrocytes isolated from the patient's cartilage or derived from mesenchymal stem cells are cultured and injected into the cartilage defects in liquid or gel form. The mesenchymal stem cells inhibit the release of proinflammatory cytokines and are helpful in cartilage repair and osteoarthritis (Diekman et al, 2012). The ear and nose cartilage tissue has high regeneration capacity and future therapy with iPS may not be needed for these problems.…”
Section: Cartilage Tissue Production With Ips Cells For Tissue Repairmentioning
confidence: 99%
“…However, the capacity of articular cartilage for repair and regeneration is extremely poor. iPS cells have the potential to provide an abundant cell source for tissue engineering and the generation of patient-matched in vitro models to study genetic and environmental factors in cartilage repair (Diekman et al, 2012).…”
Section: Cartilage Tissue Production With Ips Cells For Tissue Repairmentioning
confidence: 99%
“…Moreover, in this study the stem cell derived-cells did not reveal the tumorigenic risk in a mouse fracture model. In the other study, the usefulness of murine iPSCs in cartilagerepair therapies was demonstrated [57]. After initial chondrogenic differentiation, iPSCs were treated with type II collagen-driven green fluorescent protein (GFP) and the GFP positive cells were seeded onto 1% agarose, delivered to the defect and chondrogenic differentiation was successfully performed for 21 days.…”
Section: Scale-up Pluripotent Stem Cell Culturementioning
confidence: 99%
“…These cells differentiate into several cell lineages including osteogenic and chondrogenic [8,9]. More recently described induced pluripotent stem cells (iPSCs) have the potential to differentiate into somatic cells, including chondrocytes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%